Expanding the versatility of phage display II: improved affinity selection of folded domains on protein VII and IX of the filamentous phage. - Geir Åge Løset (Public Library of Science (PLoS), 2011)
Background Phage display is a leading technology for selection of binders with affinity for specific target molecules. Polypeptides are normally displayed as fusions to the major coat protein VIII (pVIII) or the minor coat protein III (pIII). Whereas pVIII display suffers from drawbacks such as heterogeneity in display levels and polypeptide fusion size limitations, toxicity and infection interference effects have been described for pIII display. Thus, display on other coat proteins such as pVII or pIX might be more attractive. Neither pVII nor pIX display have gained widespread use or been characterized in detail like pIII and pVIII display. Methodology/principal findings Here we present a side-by-side comparison of display on pIII with display on pVII and pIX. Polypeptides of interest (POIs) are fused to pVII or pIX. The N-terminal periplasmic signal sequence, which is required for phage integration of pIII and pVIII and that has been added to pVII and pIX in earlier studies, is omitted altogether. Although the POI display level on pIII is higher than on pVII and pIX, affinity selection with pVII and pIX display libraries is shown to be particularly efficient. Conclusions/significance Display through pVII and/or pIX represent platforms with characteristics that differ from those of the pIII platform. We have explored this to increase the performance and expand the use of phage display. In the paper, we describe effective affinity selection of folded domains displayed on pVII or pIX. This makes both platforms more attractive alternatives to conventional pIII and pVIII display than they were before.